THE IMPLEMENTATION OF COLLABORATIVE STRATEGY IN TEACHING STUDENTS’ READING COMPREHENSION OF THE TENTH GRADE OF SMK NEGERI 1 SITOLU ORI IN 2022/2023 - Telaumbanua, Prety Kirana Septania; Telaumbanua, Yasminar Amaerita; Harefa, Hasrat Sozanolo; Zega, Riswan (Jurnal Review Pendidikan dan Pengajaran, 2023)
Collaborative Strategy is a learning model used by teachers in the teaching and learning process in groups. Collaborative Strategy can help students to interact with their friends in reading comprehension. The aim of this research is to analyze the implementation of Collaborative Strategy in teaching students' reading comprehension. This research used a descriptive qualitative approach, which is a research method used to search on natural object conditions. The research instruments used were Lesson Plan, Observation Sheet, Field Notes, Students' Worksheet, and Transcript Interview. The results showed that the implementation of Collaborative Strategy in teaching students' reading comprehension ran well. It was proven that when doing collaborative students the interacted with fellow friends. For students' comprehension level, students in class X TKJ 2 at SMK Negeri 1 Sitolu Ori are at the literal meaning level with the result that 80% of the answers at this level. The results of Collaborative Strategy implementation challenges were decoding 38% with 8 students, fluency 9% with 2 students, vocabulary 24% with 5 students, sentence construction and cohesion 9% with 2 students, reasoning and background knowledge 10% with 2 students, working memory and attention 10% with 2 students.